2022
DOI: 10.1039/d2ra03345c
|View full text |Cite
|
Sign up to set email alerts
|

A controllable one-pot hydrothermal synthesis of spherical cobalt ferrite nanoparticles: synthesis, characterization, and optical properties

Abstract: A controllable synthesis of spherical cobalt ferrite nanoparticles with average crystallite size in the range of 3.6–12.9 nm using a facile, eco-friendly, hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The lattice fringes of as-prepared CPCF NPs can be seen obviously in Fig. 6 C, the adjacent fringe spacing is about 0.253 nm, corresponding to the (311) lattice planes of Co Fe 2 O 4 NPs 47 , 48 . it can be seen the particles are nano sized and revealed it is in cubic shape and the average particle size of 18 nm which is agree well with the XRD result.…”
Section: Resultsmentioning
confidence: 94%
“…The lattice fringes of as-prepared CPCF NPs can be seen obviously in Fig. 6 C, the adjacent fringe spacing is about 0.253 nm, corresponding to the (311) lattice planes of Co Fe 2 O 4 NPs 47 , 48 . it can be seen the particles are nano sized and revealed it is in cubic shape and the average particle size of 18 nm which is agree well with the XRD result.…”
Section: Resultsmentioning
confidence: 94%
“…In the TEM micrograph of the prepared MNP, it is clear that the obtained NPs are in a polygon shape with a size distribution from 15 to 70 nm (Figure a). The FT-IR spectrum of the MNP shows that the dominating signal at 567 cm –1 is due to Fe–O, which confirms the formation of iron oxide (Fe 3 O 4 ) . While the peak at 1631 cm –1 is corresponding to O–H bending, which confirmed the presence of hydroxyl groups on the MNP surfaces.…”
Section: Resultsmentioning
confidence: 75%
“…The FT-IR spectrum of the MNP shows that the dominating signal at 567 cm −1 is due to Fe−O, which confirms the formation of iron oxide (Fe 3 O 4 ). 57 While the peak at 1631 cm −1 is corresponding to O−H bending, which confirmed the presence of hydroxyl groups on the MNP surfaces. The peak observed at 3437 cm −1 is ascribed to O−H starching, indicating the presence of water molecules (Figure 2b).…”
Section: Iron Oxide Npsmentioning
confidence: 71%
“…For example, Lu et al 27 reported that cobalt ferrite nanoparticles with a cubic morphology can be obtained using a hydrothermal route when a 1 : 1 molar ratio of cobalt and iron precursors is used. Refat et al 28 showed that the purity and crystallinity of CoFe 2 O 4 obtained through hydrothermal synthesis can be maintained at 180 °C. Also, in the case of NGO, it has been shown previously 29 that hydrothermal synthesis using N 2 H 4 at a lower temperature has unreacted nitride content adsorbed on the GO surface, whereas in hydrothermal treatment at a higher temperature of 180 °C, the reduction of GO using N 2 H 4 and ammonia affords more graphitic/pyridine N-incorporated into the carbon network of graphene sheets.…”
Section: Materials Characterizationmentioning
confidence: 99%